(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
This study presents a detailed comparison of energy consumption between green and conventional commercial buildings by analyzing actual energy usage against benchmarks derived using Multiple Linear Regression (MLR) and Building Energy Intensity (BEI). MLR, selected for its statistical robustness and ease of implementation, incorporates variables such as Cooling Degree Days (CDD), temperature, humidity, rainfall intensity, wind speed, and number of working days as independent factors. The study evaluates energy consumption across 20 office buildings in Klang Valley, Malaysia, from 2019 to 2023. The findings indicate that both green and conventional buildings generally consumed less energy than their benchmarks. In terms of the difference between actual energy consumption and the benchmarks; green buildings recorded a narrower gap (26.49%) than conventional buildings (34.99%). However, green buildings consistently achieved superior energy efficiency, with BEI values ranging from 110 to 150, compared to 170 to 220 for conventional buildings. A notable reduction in energy usage occurred from 2020 to 2021 due to COVID-19-related remote work environment, though BEI slightly increased in 2023 with the normalization of operations. Energy label ratings further highlighted green buildings’ superior performance, with 42% achieving a 4-star rating, while 80% of conventional buildings received only 2-star ratings. The results emphasize the importance of green building practices, demonstrating their long-term benefits in reducing energy consumption and achieving higher energy efficiency for sustainable living. This study offers valuable insights for policymakers, developers, and stakeholders, underscoring the need for sustained efforts in energy saving and innovation to enhance building energy performance.